Metagenomics-Based Discovery of Malachite Green-Degradation Gene Families and Enzymes From Mangrove Sediment - Qu, Wu; Liu, Tan; Wang, Dexiang; Hong, Guolin; Zhao, Jing (Frontiers in Microbiology, 2018)
Malachite green (MG) is an organic contaminant and the effluents with MG negatively influence the health and balance of the coastal and marine ecosystem. The diverse and abundant microbial communities inhabiting in mangroves participate actively in various ecological processes. Metagenomic sequencing from mangrove sediments was applied to excavate the resources MG-degradation genes (MDGs) and to assess the potential of their corresponding enzymes. A data set of 10 GB was assembled into 33756 contigs and 44743 ORFs were predicted. In the data set, 666 bacterial genera and 13 pollutant degradation pathways were found. Proteobacteria and Actinobacteria were the most dominate phylum in taxonomic assignment. A total of 44 putative MDGs were revealed and possibly derived from 30 bacterial genera, most of which belonged to the phylum of Proteobacteria and Bacteroidetes. The MDGs belonged to three gene families, including peroxidase genes (up to 93.54% of total MDGs), laccase (3.40%) and p450 (3.06%). Of the three gene families, three representatives (Mgv-rLACC, Mgv-rPOD and Mgv-rCYP) which had lower similarities to the closest sequences in data bank were prokaryotic expressed and their enzymes were characterized. Three recombinant proteins showed different MG-degrading activities. Mgv-rPOD had the strongest activity which decolorized 97.3% of MG (300 mg/L) within 40 min. Additional, Mgv-rPOD showed a more complete process of MG degradation compared with other two recombinat proteins according to the intermediates detected by LC-MS. Furthermore, the high MG-degrading activity was maintained at low temperature (20°C), wider pH range, and the existence of metal ions and chelating agent. Mgv-rLACC and Mgv-rCYP also removed 63.7% and 54.1% of MG (20 mg/L) within 24 h, respectively. The results could provide a broad insight into discovering abundant genetic resources and a effective strategy to access the eco-friendly way for preventing coastal pollution.